Clinical Evaluation of Corneal Endothelium and Central Corneal Thickness Before and After Cataract Surgery - Shrestha, Poonam; Mikarani, Neyaz Kausar; Budhathoki, Om Prakash; Paudel, Santosh (Nepalese Journal of Ophthalmology, 2025)
Introduction: Preservation of corneal endothelial function is a major goal in cataract surgery as it plays an important role in maintaining the corneal transparency and visual outcome. This study compared the morphological features of corneal endothelium and central corneal thickness (CCT) before and after cataract surgery. Objective: To compare the corneal endothelium morphology and central corneal thickness before and after cataract surgery. Methodology: This was hospital-based, prospective, observational study conducted at Nepal eye hospital within six months period from September 2022 to February 2023 considering inclusion and exclusion criteria before and after cataract surgery, that is Phacoemulsification. Consecutive sampling technique was utilised and ethical approval was taken. Corneal endothelial cell characteristics: endothelial cell density, coefficient of variability, percentage of hexagonality, and central corneal thickness were taken before the surgery and then first week and six weeks after cataract surgery. Result: Among the 63 patients were who underwent cataract surgery the mean age was 69.81±9.2 years with male:female ratio of 31:32. The mean CCT preoperatively, first week, and six weeks after surgery were 536.06±34.3, 536.46±41.9, and 523±37.9 respectively which suggest slight borderline statistical difference in CCT preoperatively and at six weeks. The endothelial loss at first week follow-up was 22.5% and the preoperative hexagonality was 64.83±6.56, and at one week follow up the hexagonality decreased to 62.14± 6.99 which was statistically significant. The endothelial cell loss at six week follow up was 24.8%, polymegathism was increased and percentage of hexagonality had decreased. Conclusion: Endothelial cell alteration after surgery is important parameter for estimation the safety of surgical technique. The study concluded that there were changes in corneal endothelial morphology and central corneal thickness before and after cataract surgery.